2006
DOI: 10.1073/pnas.0605993103
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine targets cycling B cells independent of receptors/transporter for oxidative attack: Implications for non-Hodgkin’s lymphoma

Abstract: Human B lymphocytes and derived lines from a spectrum of B cell malignancy were studied for expression of dopaminergic pathway components and for their cytostatic response to the catecholamine and related, potentially therapeutic compounds. Proliferating normal lymphocytes and dividing malignant clones rapidly arrested on exposure to dopamine in the low (<10 M) micromolar range. The antiparkinsonian drugs L-DOPA and apomorphine (particularly) were similarly antiproliferative. With the exception of D4, dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 46 publications
5
74
0
3
Order By: Relevance
“…EAE is mediated mainly by T cells, but B cells also contribute to the initiation and development of the disease (43,45,46). Type I DARs as well as serotonin receptors have been found to be expressed on many types of immune cells including DCs (47), T cells (23,48,49), and B cells (50,51). Therefore, systemic treatment with SCH could affect several types of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…EAE is mediated mainly by T cells, but B cells also contribute to the initiation and development of the disease (43,45,46). Type I DARs as well as serotonin receptors have been found to be expressed on many types of immune cells including DCs (47), T cells (23,48,49), and B cells (50,51). Therefore, systemic treatment with SCH could affect several types of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 Apoptotic pathway activation after treatment with the IC 50 concentrations of each agent was evaluated by PCR analysis of caspase 3 transcript and measurement of caspase 3 activity using the PhiPhiLux assay. 23,24 Finally, flow cytometric analysis was performed and cell cycle alterations were examined in response to IC 50 concentrations of each compound over a 72-hour period (2 population doubling times for each cell line 20,21 ). The requirement for trypsin digest with the associated cell death in the adherent NCI-H727 cell line precluded flow cytometric analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Cas-pase-3 activity was evaluated using the PhiPhiLux G1D2 kit (MBL, Nagoya, Japan) as described. 23,24 A substrate of PhiPhiLux G1D2, which can penetrate into the cell nucleus, is converted to the fluorescent form when cleaved by the protease activity of caspase-3. The assessment was performed according to the manufacturer's recommendations.…”
Section: 30mentioning
confidence: 99%
“…[32][33][34][35] Similarly, neuropeptides and neurotransmitters that have key functions in the central and peripheral nervous systems can exert immune modulatory effects. 2,5,36 Indeed, emerging data demonstrate that these molecules can be transported or expressed by hematopoietic cells. 24,37,38 In our previous study, we demonstrated that DCs take up and sequester 5-HT in lysosomal vesicles for subsequent release via Ca 2ϩ -triggered exocytosis.…”
mentioning
confidence: 99%